Modernisasi Pendidikan oleh Kyai Wahid Hasyim di Pesantren Tebuireng, 1934-1953 - Bayu Bintoro (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This article aims to analyze the modernization of education that occurred at the Tebuireng pesantren during the Kyai Wahid Hasyim era. The problems raised in this study are: 1) how was the condition of the Tebuireng Islamic boarding school in 1934-1953; 2) how the modernization of the education system at the Tebuireng Islamic boarding school was; 3) Why the modernization of the Tebuireng Islamic boarding school education occurred in the changes in institutions and learning systems. The method used is the historical method which consists of four steps, namely heuristics, verification, interpretation, and historiography. The limitation or focal point of this research is modernization at the time of Kyai Wahid Hasyim. The results showed that the modernization of the Tebuireng pesantren was carried out by Kyai Wahid Hasyim after returning from Mecca. Modernization is carried out so that santri can compete with the outside world, in order to contribute to the community, and as a form of improving general education in pesantren.